Four new troglobiotic species of the genus Megalothorax Willem, 1900 (Collembola: Neelipleona) from the Carpathian Mountains (Slovakia, Romania) - Papáč, Vladimír; Kováč, Ľubomír (Zootaxa, 2013)
Four new species of Megalothorax Willem, 1900 are described and illustrated: M. tatrensis sp. nov., M. carpaticus sp. nov., M. hipmani sp. nov. from caves in Slovakia and M. draco sp. nov. from the Drǎcoaia Cave in western Romania. The species represent troglobiotic forms exhibiting different level of troglomorphy involving such features as larger body, elongated foot complex, antennae, mucro and body chaetae. The most pronounced troglomorphy is observed in M. hipmani sp. nov. and M. draco sp. nov. Species descriptions are completed with comparative tables of chaetotaxy of antennae and legs. Diagnostic table for all congeners and dichotomous identification key to the world species are provided. Distribution records of other Megalothorax species in Slovakia are added.